On generalized partition methods for interaction energies. Issue 42 (22nd October 2020) - Racioppi, Stefano; Sironi, Angelo; Macchi, Piero
Abstract : The breakdown of interaction energy has always been a very important means to understand chemical bonding and it has become a seamlessly useful tool for modern supramolecular chemistry. Abstract : The breakdown of interaction energy has always been a very important means to understand chemical bonding and it has become a seamlessly useful tool for modern supramolecular chemistry. Many interaction schemes and partitioning methods are known and widely adopted. Their common mechanism is the fragmentation of a chemical system into smaller moieties and the identification of interaction energy contributions somewhat related to a physical phenomenon. However, the definitions of energy terms and of the molecular fragments are not universal, leading to complicated comparisons among different approaches and controversial interpretations. The most adopted methodologies use a partition of the Hilbert space or of the position space. In this paper, we propose a protocol to compare energy decomposition methods based on two schemes representative of each category, namely the energy decomposition analysis (EDA, Hilbert space) and the interacting quantum atom (IQA, position space).